1981
DOI: 10.1111/j.1365-2265.1981.tb02963.x
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's Disease Presenting as Amenorrhoea With Hyperprolactinaemia: Report of Two Cases

Abstract: Two patients with Cushing's disease first presented with amenorrhoea, hyperprolactinaemia, and normal tomograms of the sella turcica. Both women underwent trans-sphenoidal removal of a pituitary microadenoma resulting in a decreased serum prolactin concentration in both, and cessation of galactorrhoea and return of menses in one of them. One woman became ACTH deficient while the other has persistent Cushing's disease. A survey of the literature on Cushing's disease and prolactinomas shows the association to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…This hypothesis is supported by exist¬ ing evidence that pituitary tumours may secrete other hormones (Müller et al 1978;Heitz 1979;Bassetti et al 1986;Melmed et al 1986;Rehfeld et al 1987). In particular, an association between Cushing's disease and hyperprolactinaemia has been documented previously (Caufriez et al 1981;Jurney et al 1981;Yamaji et al 1984), one series reporting elevated PRL levels in 23% of patients with Cushing's disease and in 50% of patients with Nelson's syndrome (Yamaji et al 1984). In addition, immunocytochemical localisa¬ tion of PRL in corticotrope adenomata (Sherry et al 1982;Yamaji et al 1984) and correlation between ß-endorphin and PRL secretion by pitu¬ itary adenoma cells in culture have been described (Yamaji et al 1985).…”
Section: )mentioning
confidence: 68%
See 1 more Smart Citation
“…This hypothesis is supported by exist¬ ing evidence that pituitary tumours may secrete other hormones (Müller et al 1978;Heitz 1979;Bassetti et al 1986;Melmed et al 1986;Rehfeld et al 1987). In particular, an association between Cushing's disease and hyperprolactinaemia has been documented previously (Caufriez et al 1981;Jurney et al 1981;Yamaji et al 1984), one series reporting elevated PRL levels in 23% of patients with Cushing's disease and in 50% of patients with Nelson's syndrome (Yamaji et al 1984). In addition, immunocytochemical localisa¬ tion of PRL in corticotrope adenomata (Sherry et al 1982;Yamaji et al 1984) and correlation between ß-endorphin and PRL secretion by pitu¬ itary adenoma cells in culture have been described (Yamaji et al 1985).…”
Section: )mentioning
confidence: 68%
“…We have used this technique for investiga¬ tion of patients with Cushing's syndrome over the past 2 years and have observed that several other pituitary hormones were consistently elevated in parallel with the ACTH sinus gradients, despite normal peripheral levels of the non-ACTH hor¬ mones. Although elevation of hormones other than ACTH has been described in pituitary Cush¬ ing's disease, the phenomenon is uncommon (Muller et al 1978;Caufriez et al 1981;Jurney et al 1981;Sherry et al 1982;Yamaji et al 1984). This study reports a detailed analysis of the pat¬ tern of pituitary secretion of various hormones in patients with pituitary dependent Cushing's di¬ sease due to microadenomata.…”
mentioning
confidence: 90%
“…From studies in man it has been concluded that pituitarydependent Cushing's syndrome is associated with an intrinsic disturbance in the regulation of prolactin (PRL) secretion (Croughs, Rijnberk and Meijer 1979). In patients with Cushing's disease the plasma prolactin levels are normal (Krieger, Howanitz and Frantz 1976) or slightly elevated (Lamberts, Timmermans, deJong and Birkenhdger 1977;Caufriez, Desir, Szyper, Robyn and Copinschi 1981 ;Jurney, de Ruyter and Vigersky 1981), whereas in normal individuals corticosteroid administration results in decreased PRL levels (Sowers, Carlson, Brautbar and Hershman 1977;Copinschi, L 'Hermite, Le Clercq, Golstein, Van Haelst, Virasoro and Robyn 1975). Furthermore, the response of plasma PRL to thyrotrophin releasing hormone (TRH) has been reported to be normal (Krieger, Howanitz and Frantz 1976;Lamberts et al 1981) in pituitary-dependent Cushing's disease, whereas corticosteroid administration to normals is associated with decreased responsiveness (Copinschi et al 1975).…”
Section: Introductionmentioning
confidence: 99%
“…[343] Για τον λόγο αυτό συνιστάται ο έλεγχος και των υπόλοιπων ορµονών του πρόσθιου λοβού της υπόφυσης σε γυναίκες µε διαταραχές εµµηνορρυσίας/αµηνόρροια και υπερπρολακτιναιµία. [344]…”
Section: παθήσεις των επινεφριδίωνunclassified